STUDI DAMPAK BENCANA KOTA PALU TERHADAP DISTRIBUSI MATERIAL BATU GAJAH DAN BRONJONG KE KABUPATEN PASANGKAYU - Kartini, Kartini; Ali, Amar; Jokolelono, Eko (Katalogis, 2021)
The purpose of this study was to determine the impact of the Palu City disaster on the distribution of elephant and gabion stone material to the City of Pasangkayu. For data collection techniques, the author uses observation, questionnaires, interviews, and documentation. The research results show that it can be concluded that the natural disasters that occurred in Palu City also had an impact on the distribution of goods from the city to surrounding areas, such as the City of Pasangkayu, which depended on the material needs for elephants and gabions on the City of Palu. stopped the distribution of these materials to Pasangkayu City for some time, this clearly resulted in the development of Pasangkayu City being stopped for a while. Although a few moments later the material distribution activity resumed, but it was not really running normally, the length of post-disaster recovery made elephant stone production activities and gabion distribution from producers to distributors in Palu City not really running normally, So that scarcity due to limited stock of elephant and gabions is something that must be dealt with, and obviously this problem has led to an increase in the price of both materials. The purpose of this study is to determine the impact of the Palu City disaster on the distribution of elephant and gabion stone materials to Pasangkayu Regency. For data collection techniques, the author uses observation, questionnaires, interviews, and documentation.